Acceptance of Mobile Marketing Amongst Generation Z Students in South Arica: The Moderating Role of Attitude - Koloba, Habofanwe Andreas; Surtie, Sumaya Sunaida (Acta Universitatis Danubius. Œconomica, 2023)
Mobile marketing distinguishes itself from other forms of marketing and serves to boost sales. However, research on Generation Z attitude on mobile marketing is scant even though this generation is an important segment of the consumer market. The purpose of this study was to investigate the moderating role of attitude on the relationship between factors influencing mobile marketing acceptance and the acceptance of mobile marketing amongst Generation Z students in South Africa. Previous research has revealed that consumers are very sensitive and protective of their privacy and do not always allow marketers to deliver messages without their permission. This study followed a quantitative approach and data were collected by means of a self-administered questionnaire amongst Generation Z students. A hierarchical multiple regression analysis was used to assess the moderating role of attitude. The results revealed that Generation Z students’ attitude moderates the relationship between the identified four factors, namely perceived ease of use, perceived usefulness, trust and risk and the acceptance of mobile marketing. Therefore, marketers should align their mobile marketing activities with Generation Z cohort in mind as their attitude towards mobile marketing strengthens their acceptance.